2014
DOI: 10.1590/0104-07072014002920012
|View full text |Cite
|
Sign up to set email alerts
|

The ways in which blind mothers cope with taking care of their children under 12 years old

Abstract: This study was aimed at analyzing the ways in which blind mothers cope with taking care of their children under 12 years old and is focused on health promotion, risk prevention and education. This is a qualitative study held in Fortaleza, in the state of Ceará, at the homes of nine blind mothers. A semi-structured interview was performed, from which the core meanings emerged: suitability of the home environment in order to prevent domestic accidents; prevention and treatment of diseases and monitoring of educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
1
4
0
7
Order By: Relevance
“…Os sete estudos identificados [24][25][26][27][28][29][30] podem ser observados na Figura 2, em que aparecem os dados sintetizados, mostrando em qual base de dados e periódico foi encontrado, título, ano de publicação, qual foi o foco de cada estudo bem como seus participantes. Estes foram agregados a partir das semelhanças encontradas nos estudos, com o intuito de contribuir com a análise das categorias: Interação mãe-filho; A vivência da maternidade de mães cegas.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Os sete estudos identificados [24][25][26][27][28][29][30] podem ser observados na Figura 2, em que aparecem os dados sintetizados, mostrando em qual base de dados e periódico foi encontrado, título, ano de publicação, qual foi o foco de cada estudo bem como seus participantes. Estes foram agregados a partir das semelhanças encontradas nos estudos, com o intuito de contribuir com a análise das categorias: Interação mãe-filho; A vivência da maternidade de mães cegas.…”
Section: Resultsunclassified
“…Foi utilizado o enfrentamento como abordagem teórica e entrevista semiestruturada para coleta dos dados. O resultado da análise das entrevistas foi categorizado em três temáticas de análise: adequação do ambiente domiciliar para a prevenção de acidentes domésticos; estratégia de promoção da saúde e cuidado com os filhos e acompanhamento da vida escolar 29 .…”
Section: A Vivência Da Maternidade De Mães Cegasunclassified
See 2 more Smart Citations
“…This is able to care for their children which imply on the understanding of health professionals on the subject, which is not well known. The family should be included in monitoring their children so that assistance is safe and effective, with strengthening of its autonomy and independence [20]. Study found that the blind parents find strategies to care for their children who rely on the remaining senses (touch, smell and hearing) and the use of support networks, as a mother, sister or community was essential for assistance in caring for blind mother [21].…”
Section: Discussionmentioning
confidence: 99%